EVALUATION OF THE CIPP MODEL IN ENHANCING THE INTERNALIZATION OF ISLAMIC VALUES AT TK TUNAS KUSUMA BANGSA, DUKUH BUMIREJO, MUNGKID, MAGELANG - Mu'arifah, Nurvianna; Muhlil Musolin (CV. Fahr Publishing, 2024)
This study aims to evaluate the implementation of Islamic Religious Education (PAI) in supporting the internalization of Islamic values at TK Tunas Kusuma Bangsa, Dukuh Bumirejo, Mungkid District, Magelang Regency. The evaluation model applied in this research is the CIPP model (Context, Input, Process, Product) developed by Stufflebeam. Using a descriptive-qualitative approach, the study provides a comprehensive analysis of the effectiveness of PAI learning in Islamic-based early childhood education. Data were collected through observation, interviews, and documentation, and analyzed using Miles & Huberman's interactive model. Context evaluation indicates that the school’s vision and mission are aligned with the goal of fostering Islamic character. Input evaluation shows that teachers have relevant educational backgrounds and learning media are sufficiently available, although teacher training in value integration remains limited. Process evaluation reveals varied instructional methods, yet still tends to be normative and lacks reflective value internalization. Product evaluation shows positive signs of religious behavior among children, though still in early habituation stages. The study concludes that the CIPP model is effective in providing a holistic overview of PAI learning quality and can serve as a basis for improvement through teacher training, enrichment of learning media, and parental involvement. This research contributes to the development of value-based evaluation models in early childhood education.